Dementia and gender in public forum discourses - Kleinke, Sonja; Pleyer, Monika (Discourse, context & media, 2025)
Though gender differences have been attested in medical research as well as qualitative offline interview studies, public societal dementia discourses often oscillate between practices of ‘de-gendering’ and applying double standards when representing people with dementia. Against this background, there is a dearth of research into family care partners’ bottom-up construction of gender in online forum interactions, including how care partners understand and depict their person living with dementia in participatory forum contexts. Applying a dynamic discursive approach to pertinent public threads from Dementia Support Forum (Alzheimer’s Society UK), our paper aims to answer two central questions: Are there gender-related patterns of participation in the discussions? And (how) do care partners gender their person living with dementia explicitly or implicitly in different mediated micro-contexts of forum interaction? Our study reveals that in these forum discussions, gendering has relevance at three levels: the meta-discursive level of participation patterns, explicit ascriptions of gender roles and, implicitly, in correlations with dementia-related conduct. Our findings also indicate that the concrete practices of gendering may, at least partly, be determined by their respective mediated micro-contexts; communal threads may tacitly encourage users to apply double standards implicitly while long-term diary threads leave more room for explicit identity-maintaining gendering.
Online verfügbar: 01. November 2025
Gesehen am 17.02.2026